2019
DOI: 10.1371/journal.pone.0215145
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive qualitative and semiquantitative presurgical investigation of the feeding vasculature to intracranial meningiomas using superselective arterial spin labeling

Abstract: Background Intracranial meningiomas may be amenable to presurgical embolization to reduce bleeding complications. Detailed information usually obtained by digital subtraction angiography (DSA) on the contribution of blood supply from internal and external carotid artery branches is required to prevent non-target embolization and is helpful for pre-surgical planning. Purpose To investigate the contribution of the feeding vasculature to intracranial meningiomas with super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To this end, preoperative embolization of tumors with abnormal blood supply is encouraged when necessary to reduce intraoperative bleeding and facilitate the surgery. Super-selective embolization of intratumoral vessels [ 12 ] refers to the delivery of a microcatheter into the blood supply artery of a meningioma patient, through which an embolic agent is injected to block the blood flow, prevent intraoperative bleeding, and soften the tumor, thereby reducing the difficulty of surgical resection and facilitating surgical resection [ 13 , 14 ]. However, due to the paucity of related clinical studies, the clinical effectiveness of this procedure has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, preoperative embolization of tumors with abnormal blood supply is encouraged when necessary to reduce intraoperative bleeding and facilitate the surgery. Super-selective embolization of intratumoral vessels [ 12 ] refers to the delivery of a microcatheter into the blood supply artery of a meningioma patient, through which an embolic agent is injected to block the blood flow, prevent intraoperative bleeding, and soften the tumor, thereby reducing the difficulty of surgical resection and facilitating surgical resection [ 13 , 14 ]. However, due to the paucity of related clinical studies, the clinical effectiveness of this procedure has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These labeling spots, generated by rotating gradients with phase changes in radiofrequency pulses of pCASL labeling trains, are flexibly positioned, adapting to individual vessel geometries. 12,15 As in previous studies, 15,18 we successfully placed labeling spots on ICAs, ECAs, and the VA without much difficulty, even in patients with tortuous vessels. However, labeling is reliant on preacquired TOF-MRA images, so even slight interim shifts in patient positions (between TOF-MRA and labeling) may interfere, leading to partial or no overlay of targeted arterial labeling spots.…”
Section: Discussionmentioning
confidence: 58%
“…[11][12][13] A number of studies have shown the merit of this technique in certain cerebrovascular disorders such as arteriovenous malformations and carotid artery stenosis, 14,15 but the few efforts to date exploring its applicability to meningioma have lacked full comparisons with DSA. [16][17][18] The present study provides a comparative analysis of superselective pseudocontinuous ASL (ss-pCASL) 12 and DSA in patients with meningiomas, each used to define feeding vessels and gauge preoperative embolization feasibility. We hypothesized that ss-pCASL would reliably predict feeding vasculature of meningiomas.…”
mentioning
confidence: 99%